Consensual conjugal unions among higher educated women: understanding the heterogeneity in the Brazilian context - Mariana de Araújo Cunha; Ana Paula Verona (Revista Brasileira de Estudos de População, 2022)
Abstract Consensual unions have increased greatly in Brazil over the last few decades. Initially, restricted to less-educated groups, they have now been observed in all educational groups, leading some to suggest a diffusion of the Second Demographic Transition (SDT) in the country. In this paper, we examine the characteristics of women choosing consensual unions in Brazil between 1980 and 2010, with a focus on differentials by education. The results show that higher educated women, when compared to the least educated group, prefer marriage over consensual union both in 1980 and 2010. In addition, we show a growing difference between educational groups over time for choosing informal unions, as the probabilities for higher educated women to choose this type of union have increased less than for lower educated ones. For women with high educational levels in 2010, the likelihood of being in a consensual union is greater than among those from lower socioeconomic groups and among blacks, browns, and Catholics. Our results question the explanations given by the SDT for the expansion of consensual unions in upper socioeconomic groups in Brazil.